HABITUS PATRIARKI DAN KEKERASAN SIMBOLIK: DEKONSTRUKSI STRATIFIKASI GENDER DALAM KOSMOLOGI JAWA TRADISIONAL - Binti Hadziqotun Nashihah; Binti Maunah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the forms of gender-based social stratification in traditional Javanese culture, as well as the factors that cause it and its impact on Javanese society. This study focuses on how cultural values, social norms, and gender role constructions are passed down from generation to generation, which then form unbalanced patterns of relations between men and women. The method used is a literature study by reviewing relevant literature in the form of credible and relevant books, journals, and research reports, thereby obtaining a comprehensive understanding without collecting field data. The results show that gender social stratification in traditional Javanese culture is strongly influenced by a patriarchal system that limits women's roles to the domestic sphere, while men dominate the public sphere. This inequality is reflected in cultural norms, gender stereotypes, and rigid role divisions, which cause women to experience subordination and limited access to education, employment, and public participation. Efforts to reinterpret Javanese cultural concepts such as kanca wingking and swarga nunut neraka katut not only as traditional norms but also as symbolic practices that still operate in gender relations in modern Javanese society. Thus, this study shows that the patriarchal cultural heritage has not been completely abandoned, but rather reproduced in a more subtle form amid the discourse of contemporary gender equality.